Development of augmented reality media in science education on the topic of earth and the solar system - Rozalina Rozalina; Faiza Rini; Felia Siska (Journal of Computer-based Instructional Media, 2025)
This study aimed to develop and evaluate Augmented Reality (AR)-based learning media for the Earth and Solar System topics in middle school science education. Using the Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the study developed AR media designed to enhance student understanding of complex scientific concepts. The effectiveness of the AR media was assessed through Aiken's V validation, practicality tests from teachers and students, and pre-test and post-test evaluations. The results showed that the AR media significantly improved student engagement, understanding, and academic performance. Aiken's V validation scores for usability, information, and interaction quality were above 0.8, indicating that the media was valid and effective. The practicality test revealed that teachers rated the media highly (93% usability), while students gave slightly lower ratings (81% usability). The N-gain score from pre-test and post-test evaluations showed a 56.2% improvement in students' knowledge, confirming the positive impact of the AR media on learning outcomes. Despite the challenges with usability for some students, the overall feedback supports AR's potential in enhancing science education, especially in rural settings. The study recommends further research to overcome usability challenges and optimize AR's classroom integration.